Construction Sustainability & Awareness amongst Contractors in the Northern Region of Malaysia - Ahmad Yusni Bahaudin; Ezanee Mohamed Elias; Mohd. Nasrun Mohd. Nawi; Nizamuddin Zainuddin; Santhirasegaran Nadarajan (International Journal of Supply Chain Management, 2017)
The level of awareness of sustainable and green practices in construction projects in Malaysia is still unsatisfactory. Even though it is increasing, the response and progress rate should be made higher to meet global standards. Sustainability in construction brings uncountable benefits to the social, environmental and economic sectors. This type of construction approach should be taken seriously as 24% of the total carbon dioxide is produced from the construction industry in this country. The aim of this research is to promote a sustainable environment in the construction proximity. Therefore, the objective of this paper is to investigate the level of commitment contractors in the northern part of Malaysia have, with regards to sustainable and green construction practices. The level of collaboration between the government and private sector will also be investigated. To investigate the degree of appreciation, a general interview guide approach with qualitative analysis is utilized as it allows the collection of general information from the interviewees. There are a number of green building rating tools being developed by various organizations in Malaysia, however, for the purpose of this research, only the GBI will be considered during analysis. It is found that less than one percent of construction projects in Malaysia are certified as green and sustainable. It is therefore recommended that in future researches, a broader spectrum of respondents should be investigated. Keywords contractors, green construction, private sector, sustainability